PENGARUH ANALISIS JABATAN TERHADAP PENCAPAIAN KINERJA PEGAWAI DINAS SOSIAL KOTA PROBOLINGGO - Mastina Maksin; Diva Putri Anindita; Hikmah Rahmadaniati Primania (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
Position analysis has a very important role in managing human resources, namely improving the insights, knowledge and performance of the organization to achieve the main objectives of the organization. From the results of the analysis of the position, the organization will be able to determine what kind of characteristics a prospective employee must have before occupying a position, the output is in the form of job specifications and job descriptions. The purpose of this study is to know and explain the magnitude of the influence of position analysis, on the achievement of employee performance. This research uses qualitative research method with descriptive analysis. This research resulted in the finding that position analysis becomes one of the most important processes in achieving employee performance in a government organization or government agency. Keywords : Job Analysis, Effect of Employee Performance Achievement